Extensive cerebral venous thrombosis following by COVID-19 vaccine with concomitant COVID-19 infection - Cheong, Xiong Khee; Tan, JK; Lim, CJ; Kori, N; Periyasamy P, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Coronavirus disease 2019 (COVID-19) vaccines have been introduced to the masses for just over two years. Majority reported adverse events post vaccination are minor side effect such as pain or inflammation at local injection site. Serious side effects such as thrombotic events or myocarditis are rarely reported. Cerebral venous sinus thrombosis (CVST) is a thrombotic complication that may occur within one to two weeks from vaccine administration. We illustrated a case from our centre involving a healthy young lady who presented with headache and an episode of seizure following by vaccination. She was concurrently diagnosed with CVST and COVID-19 infection later with the aid of neuroimaging. The patient's normal platelet count made the diagnosis of vaccine induced immune related thrombotic thrombocytopenia unlikely. While serious adverse events are reported, such as our case, this should not support the growing vaccine hesitancy among the public as its benefits still greatly outweigh its risk at this juncture.